Effects of Multihollow Surface Dielectric Barrier Discharge Plasma on Chemical and Antioxidant Properties of Peanut - Gebremedhin Gebremariam Gebremical; Shimelis Admassu Emire; Tarekegn Berhanu (Journal of Food Quality)
An experiment was conducted to investigate the effects of atmospheric pressure plasma generated by multihollow surface dielectric barrier discharge on chemical and antioxidant properties of peanut. Multihollow surface dielectric barrier discharge is a novel plasma device applicable in food industry applications due to the capacity of the generated plasma to treat the surface of food without changing the quality. Peanut seeds were exposed to the multihollow plasma for different plasma power (10–40 W), air flow rate (0.5–20 l/min), and time (1–15 min). The fatty acid profile, peroxide value, acid value, moisture content, total polyphenols, and antioxidant activity were evaluated during cold plasma treatment. The result revealed that, due to the variation plasma power, treatment time and air flow rate caused a decrease in unsaturated fatty acid and moisture content and increased saturated fatty acids, peroxide value, acid value, and total polyphenols of the peanut.